Analisis Pengendalian Intern Sistem Penerimaan Kas Pada PT. Pos Indonesia (Persero) Kantor Pos Pematangsiantar - Lubis, Syilmi Wildani; Hasibuan, Nur Fadhilah Ahmad (Maisyatuna, 2024)
The purpose of this research is to determine the internal control analysis of the cash receipts system at PT. Indonesian post. The data analysis method used is qualitative analysis with a case study approach. This type of research is qualitative descriptive research. The data sources used in the research used primary and secondary data sources. The data collection techniques used were observation, interviews and data reduction. At PT. The Pematangsiantar branch post was found to have not verified tasks according to their respective job desks and there was no supporting software, either in the form of a program or system. Thus, the effectiveness of internal control of the cash receipts system at PT. The Pematangsiantar City Post is not yet effective as a whole